The Effect Of Work Skills, Work Attitude, Work Knowledge On Work Competence And Employee Performance In Galaxy Mall Shuang Surabaya - Luvy Dian Mayasari; Hermien Tridayanti (NAROTAMA UNIVERSITY, Indonesia, 2019)
This study aims to analyze the influence of work skills, work attitudes, work knowledge on work competencies and analyze work skills, work attitudes, work knowledge on the performance of employees at the Shuang Galaxy Mall Surabaya.This study uses quantitative methods. By examining the effect of independent variables (work skills, work attitudes, work knowledge) on the dependent variable work competence and employee performance, the number of samples obtained was 41 people and analyzed using PLS (Partial Least Square) throughsoftware SmartPLS 3.0. The results of this study indicate that work skills, work attitudes, work knowledge have a significant effect on work competencies, work skills, work attitudes, work knowledge have a significant effect on employee performance and work competence has a significant effect on employee performance.